Strategies and Implementation of Character Education Empowerment Management through Islamic Cultural Schools (Madrasah Tsanawiyah) in Dempet District - Yulia Devi Ristanti; Eva Banowati; Subagyo Subagyo (JESS (Journal of Educational Social Studies), 2020)
Nowadays, character education is required to educate learners so they will be excellent individuals. Many schools take various ways to apply strategies to succeed in character education programs. Besides nurturing the characters at home, done by parents, the educational institution also plays a great role to develop children's characters. This research used a qualitative approach. The data were collected through in-depth interview, observation, and documentary study. The data analysis used data reduction, display, and conclusion. The findings consisted of 1) the Islamic school characterbuilding strategies in Dempet applied Islamic habituations. They were such as reading Asmaul Husna and reciting Al-Qur'an together in the morning before getting into the class and starting the learning; 2) the implementation of character educational empowerment was done through Islamic cultures in Dempet district. It could be done by providing memorization tasks of Al-Qur'an verses. Every class should have different memorization level and should apply extracurricular to educate the learners to have excellent characters, and 3) the engaged hindrances during its implementation were lacks of parents' controls. Thus, the learners tended to have bad personalities while being at school or home.